دراسة تحليلية لفجوة الطاقة الاستيعابية بالاقتصاد المصري وتوقعاتها المستقبلية في ضوء استراتيجية 2030 - صالح، محمد أحمد عبدالدايم أحمد (جامعة المنصورة - كلية الزراعة, 2019)
Absorptive capacity is defined as the ability of the economy to employ available resources efficiently to achieve economic returns and increase the rate of economic growth. The national economy is exposed to a set of structural imbalances, both internal and external, such as the gap in domestic resources, ie the lack of the value of savings on required investments and the external resources gap, ie the difference between exports and imports. The two previous cases are called a two-gap model or absorptive capacity gap. The problem of research is the emergence of the absorptive capacity gap resulting from the impact of the internal and external gaps and the decrease of current and targeted growth rates of real GDP and investment rate in light of the constant economic, social and political conditions compared to the target in 2030. The research aims to study the absorptive capacity gap of the Egyptian economy for the period (2000-2016) through five axes, the first of which dealt with the economic variables affecting the absorptive capacity, the second economic indicators affecting the absorptive capacity and the rate of economic growth, and the third predicting the economic variables and indicators affecting the absorptive capacity. During the period (2017-2030), the fourth comparative economic analysis of the absorptive capacity gap during the periods (2000-2016), (2017-2030), and finally addressed the fifth comparative analysis between the current situation calculated and targeted in the light of the strategy of sustainable development 2030. The study concluded that the absorptive capacity lies in either the inability to use accumulated savings and the inability to convert them into capital in kind to create jobs and added value that lead to reduce external dependence, which leads to increasing both consumer demand and dependence on the outside world and the deficit of the state budget The gap between current and target growth rates in accordance with the 2030 Sustainable Development Strategy has also been widened, requiring more effort and reform processes. The research recommended activating investment demand rates, restricting unnecessary consumer demand, and growing the real supply of goods and services in the short term through operating the idle capacities of different companies and factories and spreading small projects to increase the rate of foreign direct investment or grants and assistance and direct them in the field of infrastructure and investments and not directed to consumer spending. Increasing savings of individuals, family sector and institutions, restricting imports, especially government, and increasing customs duties on consumer imports, especially recreational.
تعرف الطاقة الاستيعابية بأنها قابلية الاقتصاد لتوظيف الموارد بكفاءة اقتصادية وزيادة معدل النمو الاقتصادي، ويتعرض الاقتصاد القومي لمجموعة من الاختلالات الهيكلية كفجوة الموارد المحلية أي نقص قيمة المدخرات عن الاستثمارات وفجوة الموارد الخارجية أي الفرق بين الصادرات والواردات أو نتيجة الحالتين السابقتين ويسمى نموذج ذات الفجوتين أو فجوة الطاقة الاستيعابية. وتكمن مشكلة البحث في نشوء فجوة الطاقة الاستيعابية الناتجة عن تأثير الفجوتين الداخلية والخارجية مما يعني زيادة الاعتماد على التمويل الخارجي وانخفاض العائد على الاستثمار وزيادة العجز في ميزان المدفوعات وزيادة الاقتراض الخارجي. وهدف البحث عامة إلى دراسة فجوة الطاقة الاستيعابية للاقتصاد المصري للفترة (2000-2016) من خلال خمسة محاور تناول الأول منها المتغيرات الاقتصادية المؤثرة على الطاقة الاستيعابية، والثاني المؤشرات الاقتصادية المؤثرة عليها ومعدل النمو الاقتصادي، والثالث التنبؤ بالمتغيرات والمؤشرات الاقتصادية المؤثرة عليها خلال الفترة (2017-2030)، والرابع تحليل اقتصادي مقارن لفجوة الطاقة الاستيعابية خلال الفترتين (2000-2016)، (2017-2030)، وأخيرا تناول الخامس تحليل مقارن بين الوضع الحالي والمستهدف لبعض المتغيرات المدروسة في ضوء استراتيجية التنمية المستدامة 2030. وتوصل البحث إلى أن فجوة الطاقة الاستيعابية تكمن إما في عدم القدرة على استعمال المدخرات وتحويلها إلى رأسمال عيني لخلق فرص عمل وقيمة مضافة مما يؤدي لتزايد قوي الطلب الاستهلاكي والاعتماد على العالم الخارجي وعجز الموازنة العامة للدولة، كما تبين أيضا اتساع الفجوة بين معدلات النمو الحالية والمستهدفة طبقا لاستراتيجية التنمية المستدامة 2030. وأوصى البحث بتنشيط معدلات الطلب الاستثماري وتقييد الطلب الاستهلاكي غير الضروري، ونمو العرض الحقيقي للسلع والخدمات بتشغيل الطاقات العاطلة للمصانع المختلفة وزيادة معدل الاستثمار الأجنبي المباشر وتوجيهه للبنية التحتية والاستثمارات وعدم توجيهه للإنفاق الاستهلاكي، وزيادة مدخرات الأفراد والمؤسسات، وتقييد الاستيراد وخاصة الحكومي.
Keywords: الاقتصاد المصري -- التنمية المستدامة -- التخطيط المستقبلي -- المعايير الدولية -- الجودة الشاملة